Analysis of visual elements in Barbie movie posters - Wa Ode, Rosyta Pua (Universitas Ahmad Dahlan, 2023)
As a means of promoting a movie, posters are usually short, clear, concise, and attention-grabbing, and visual elements such as illustrations of movie scenes are dominant. The meaning of a movie poster is formed through visual elements in such a way. The analysis conducted on this Barbie poster aims to find out the cause of the elements in this Barbie poster. This research uses qualitative research methods with descriptive analysis. In this research, most of the data collected are in the form of images, words and sentences where these data have meaning and can achieve a more real understanding than numbers or frequencies. To collect data for this research, researchers used observation and recording techniques. The typography used on the